External load-dependent degradation of P3HT:PC61BM solar cells: behavior, mechanism, and method of suppression. Issue 20 (10th May 2017) - Yan, Lingpeng; Yi, Jinduo; Chen, Qi; Dou, Junyan; Yang, Yongzhen; Liu, Xuguang; Chen, Liwei; Ma, Chang-Qi
Abstract : External load dependent degradation behavior of P3HT:PC61 BM solar cells is demonstrated, which can be successfully suppressed by blending with an exciton quencher of PC61 BM. Abstract : Understanding the influence of external loads on the degradation behavior of polymer solar cells (PSCs) is highly important for gaining deep insight into the degradation mechanism of PSCs, as well as for establishing standard stability test protocols for PSCs. In this paper, the degradation behavior of inverted P3HT:PC61 BM solar cells operated under different external load conditions were investigated. External load-dependent "burn-in" performance decays were demonstrated, i.e., devices degrade much faster in the open-circuit state than in the short-circuit state, where the short-circuit current ( J SC ) loss was found to dominate the decay in performance and is the parameter that is most sensitive to the load conditions. The device performance of aged cells maintained 84% of the initial value after thermal annealing, regardless of the load conditions during aging, demonstrating that the external load-dependent performance decay of the P3HT:PC61 BM cells is partially reversible. Analyzing the light intensity-dependent open-circuit voltage ( V OC ) characteristics and dark-current density–voltage ( J – V ) curves of the aged devices revealed that trap-assisted charge recombination increased in the aged devices. The appearance of PC61 BM dimers was confirmed by analyzing the products of the blend film after light illumination, which is ascribed to the main reason for the "burn-in" performance decay. The faster formation of PC61 BM dimers is directly correlated to a higher exciton concentration within the photoactive layer when the device is operated under higher load conditions, which explains the external load dependence of the performance decay. In addition to the formation of PC61 BM dimers, formation of PC61 BM clusters that leads to the nanomorphology changes during aging was ascribed to the second reason for the performance decay, which is external load independent and thermal irreversible. By blending the P3HT:PC61 BM photoactive layer with piperazine, a triplet quencher for fullerene molecules, the external load-dependent "burn-in" loss was fully suppressed, which unambiguously confirms that the initial "burn-in" loss in P3HT:PC61 BM solar cells is related to the PC61 BM excited state. The present work not only clearly demonstrates the behavior and mechanism for the external load-dependent degradation of P3HT:PC61 BM solar cells but also provides an effective way to improve the device stability.